Differences on allocation of available resources, in growth, reproduction, and survival, in an exotic gastropod of Physidae compared to an endemic one - Núñez,Verónica (2010)
Physa acuta Draparnaud, 1805 is an invasive gastropod that can affect local species. In Argentina, it is widespread and abundant, even in environments inhabited by the native species Stenophysa marmorata Guilding, 1828. Its predominance raises the question whether this could be explained by a more successful energy allocation in functional requirements (growth, reproduction and survival) compared to S. marmorata. This study was aimed at comparing growth rates, as well as survival and fecundity, between both species under laboratory conditions. Individuals born on the same day were grouped in four per aquaria and kept under controlled conditions of food, light, and temperature. Snails were weekly measured (maximum shell length), and growth rates were calculated using the Von Bertalanffy's equation. The number of eggs and survivors were grouped by week. Stenophysa marmorata was larger at birth than Physa acuta and invested more energy in growth, delaying sexual maturity. This resulted in a disadvantage in fecundity and survival compared to P. acuta, which had a lower growth rate but matured earlier and survived longer. Furthermore, the growth of P. acuta was not affected by reproduction, its reproductive period was longer, consequently with more eggs laid than S. marmorata.